2021
DOI: 10.3390/land10050451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ecological and Economic Benefits of Rural Land Integration in the Manas River Basin Oasis

Abstract: Land consolidation is an effective means of promoting the regularization of fragmented arable land, optimizing the allocation of land resources and improving the environment in farming areas, as well as an important means of increasing the economic returns of farming households, and it is important to scientifically assess the ecological and economic benefits of agricultural land consolidation. In this study, participatory rural assessment (PRA) was used to investigate, in detail, the meaning, satisfaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In terms of economic benefits, land remediation promotes rural economic development and contributes significantly to farmers' income increase, industrial development, and national economic growth. In this regard, the technical efficiency factor is the main contributor to the increase in food production and net agricultural income, and the law of marginal return of land resources in mountainous areas and the scarcity of land resources are proposed [19][20][21]. In terms of social benefits, researchers propose and verify the evaluation indexes of land remediation benefits from different perspectives of land types in the remediated areas and introduce structural equation modeling and gray correlation method for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of economic benefits, land remediation promotes rural economic development and contributes significantly to farmers' income increase, industrial development, and national economic growth. In this regard, the technical efficiency factor is the main contributor to the increase in food production and net agricultural income, and the law of marginal return of land resources in mountainous areas and the scarcity of land resources are proposed [19][20][21]. In terms of social benefits, researchers propose and verify the evaluation indexes of land remediation benefits from different perspectives of land types in the remediated areas and introduce structural equation modeling and gray correlation method for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…We found that farmer consolidation resulted in a significant increase in the cultivated land area, an increase in crop unit yield of at least 42.66%, and the average income of farmers increased by a value of RMB 4324 /ha, and water savings were all higher than 7.18 m 3 /ha. Additionally, the results showed that the benefits of land swapping were relatively obvious [5,19].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]. However, in the practice of farmland transfer and land expropriation, the concept of the multi-functional value of cultivated land has not been fully reflected in the transaction price of cultivated land and the compensation standard for land expropriation or a single economic value, thus leading to the real value of cultivated land being underestimated, greatly reducing farmers' income and hindering the development of rural areas [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Against the background of the general decrease of farmland in China, farmland in Xinjiang has increased annually (He et al, 2018;Zhang and Li, 2021) and has played an important role in maintaining China's food security strategy. The quality (Sheng et al, 2021), expansion patterns (Cai et al, 2021), water use (Hu et al, 2019), and mulch pollution (Xiong et al, 2019) of Xinjiang's farmland have attracted widespread scholarly attention, and management engineering measures such as agricultural land transfer (Wang et al, 2022;Yang and Liu, 2022) and land remediation (Liao et al, 2021) are being explored. In addition, the multifunctional value of farmland in Xinjiang has also drawn attention (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%